Topographic map analysis for driver cognitive distraction - Almahasneh, H. (Institute of Electrical and Electronics Engineers Inc., 2014)
EEG topographic mapping is used to examine the effect of the different cognitive tasks (math and decision-making problems) on drivers' cognitive state. Two simulated driving sessions, namely driving with distraction and driving without distraction are designed to investigate the impact of the secondary tasks on EEG responses and driving performance. Forty two subjects participated in this study and the topographic mapping is used to analyse the impact of secondary task on the brain activates. Hemispheric analysis shows that the most affected area during distracted driving by secondary task is the right frontal cortex region. Thus, it may be considered as a reliable spatial index for the study of cognitive distraction. Â© 2014 IEEE.